2009
DOI: 10.3928/01477447-20090501-21
|View full text |Cite
|
Sign up to set email alerts
|

Bread Mold Osteomyelitis in the Femur

Abstract: Rhizopus osteomyelitis is an uncommon and often fatal infection that usually occurs in immunocompromised patients. The infection is commonly referred to as "bread mold." The usual course of treatment is Amphotericin B, debridement, and, if needed, amputation of the affected limb. This article details a rare case of postoperative Rhizopus osteomyelitis in an otherwise healthy patient. The patient originally presented at another institution for anterior cruciate ligament repair after a ski injury. Postoperativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
0
12
1
Order By: Relevance
“…However, we experienced a case of massive distal femoral bone loss induced by fungal infection after ACL reconstruction. As the literature reviewed, only eight cases of fungal osteomyelitis with terrible bone destruction after ACL reconstruction were reported by three groups of authors [7][8][9]. Unlike the eight patients who suffered from Rhizopus, Candida albican or Phycomycoses infection, the patient reported by us was infected with Aspergillus.…”
contrasting
confidence: 52%
See 1 more Smart Citation
“…However, we experienced a case of massive distal femoral bone loss induced by fungal infection after ACL reconstruction. As the literature reviewed, only eight cases of fungal osteomyelitis with terrible bone destruction after ACL reconstruction were reported by three groups of authors [7][8][9]. Unlike the eight patients who suffered from Rhizopus, Candida albican or Phycomycoses infection, the patient reported by us was infected with Aspergillus.…”
contrasting
confidence: 52%
“…Three had reconstruction with an allograft-prosthesis composite, two with hemicylindrical allografts and one with an intercalary allograft arthrodesis. Wilkins et al [9]. described that a 51-year-old man with ACL repair developed clinical evidence of infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these fungi have been implicated in central-venous-catheter-associated fungaemia (Chan-Tack et al, 2005), peritonitis in patients undergoing continuous ambulatory peritoneal dialysis (Branton et al, 1990;Fergie et al, 1992;Nakamura et al, 1989;Nannini et al, 2003;Nayak et al, 2007;Polo et al, 1989;Serna et al, 2003), pleuritis following implantation of drainage catheters (Kimura et al, 2009), endocarditis on native (Mehta et al, 2004;Mitchell et al, 2010) and artificial heart valves (Gubarev et al, 2007;Sanchez-Recalde et al, 1999), osteomyelitis (Chaudhuri et al, 1992;Eaton et al, 1994;Lopes et al, 1995;Meis et al, 1994;Wilkins et al, 2009), and paranasal fungal balls (Goodnight et al, 1993;Kirkpatrick et al, 1979;Lahiri et al, 2001;Robey et al, 2009). Many of these infections are associated with biofilm formation (Costerton et al, 1999;Hall-Stoodley et al, 2004;Loussert et al, 2010) and were reported to exhibit a chronic course (Eaton et al, 1994;Lahiri et al, 2001;Lopes et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Wilkins reported the case of a non-immunocompromised patient with a postoperative RM osteomyelitis of the femur after anterior cruciate ligament repair. Multimodal treatment led to eradication of the disease [12]. A successful treatment of RM osteomyelitis of the right tibia in an immunocompromised patient was presented by Vashi [9].…”
Section: Discussionmentioning
confidence: 99%